Avaliação da aprendizagem: instrumentos e critérios avaliativos na formação inicial de professores - Barros, Ranyelle Lopes (2021)
This research deals with the evaluated instruments and criteria, in the context of learning assessment, by enabling reflections and dialogues, based on the experiences of undergraduate students in Biological Sciences and Chemistry. Understanding the importance of training these students, this research aims to develop a proposal for initial training, based on the statements of undergraduates on learning assessment, instruments and evaluation criteria at the Federal Institute of Education, Science and Technology of Amazonas - IFAM Campus Manaus Center. Therefore, it presents the evaluation of learning, instruments and evaluation criteria in teacher education, based on the views of Luckesi (2011), Perrenoud (1999), Pacheco (2002), Rossit and Storani (2010), among others. The research results from an exploratory and descriptive study, with a qualitative approach. For this, we used the questionnaire as an instrument, with questions that focus on the academic experiences of the undergraduates. Data were organized and interpreted using the Content Analysis Technique (Bardin, 2009), divided into three phases: 1) pre-analysis; 2) exploration of the material (coding and categorization) and 3) treatment of results: inference and interpretation of data. To evaluate the educational product, we submit to an Ad Hoc Committee, formed by specialist teachers, masters and doctors who work in basic and higher education and in training courses for teachers in public institutions. Thus, the results of the analyzes indicate that the undergraduates understand about the assessment of learning and the relevance of establishing instruments and criteria that serve to diagnose, monitor and intervene in the evaluation process, as well as pointing out that the most used instruments, from their experiences are objective and discursive tests, and little used, consider pre-tests and cooperative assessment. As for the evaluators trained by the Ad Hoc Committee, they issued a favorable opinion to the educational product, considering it valid in its objective of contributing to the training of licentiates.